The Discovery of Potent Nonstructural Protein 5A (NS5A) Inhibitors with a Unique Resistance Profile—Part 2. Issue 7 (11th April 2014) - Wakenhut, Florian; Tran, Thien Duc; Pickford, Chris; Shaw, Stephen; Westby, Mike; Smith‐Burchnell, Caroline; Watson, Lesa; Paradowski, Michael; Milbank, Jared; Stonehouse, David; Cheung, Kathy; Wybrow, Robert; et al.
Abstract In ongoing studies towards novel hepatitis C virus (HCV) therapeutics, inhibitors of nonstructural protein 5A (NS5A) were evaluated. Specifically, starting from previously reported lead compounds, peripheral substitution patterns of a series of biaryl‐linked pyrrolidine NS5A replication complex inhibitors were probed and structure–activity relationships were elucidated. Using molecular modelling and a supercritical fluid chromatographic (SFC) technique, intramolecular H‐bonding and peripheral functional group topology were evaluated as key determinants of activity and membrane permeability. The novel compounds exhibited retained potency as compared with the lead compounds, and also showed promising results against a panel of resistance viruses. Together, the results of the study take us a step closer towards understanding the potency of daclatasvir, a clinical candidate upon which the compounds were based, and to designing improved analogues as second‐generation antiviral agents targeting NS5A.